Mechanism and control system of Damping Diverters in Heat Recovery Steam Generator (HRSG) at PT. Indonesia Power, UPJP Priok, DKI Jakarta, Indonesia - Athiyyah Rieke Hisana; Dodi Sofyan Arief; Gamal Fiqih Handonowarih (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2019)
Heat Recovery Steam Generator (HRSG) is one of the components in PLTGU, HRSG used the remaining heat energy to circulate a gas turbine unit to heat the water and convert to steam, and then activate it to move the steam turbine. Water heating in HRSG is done by utilizing exhaust gas as much as possible from the gas turbine. In HRSG there is one component that is a diverter damper that functions as a diverter or regulates the amount of residual combustion gas flow from the gas turbine generator step into HRSG.